Controlling glass bead surface functionality - Impact on network formation in natural edible polymer systems. (28th July 2021) - Brandner, Silvia; Kratky, Tim; Holtz, Kerstin; Becker, Thomas; Jekle, Mario
Abstract: Combining particles and polymers provides materials with unique mechanical properties. Hereby, the character of the particle surface is important for the network properties. However, particle-polymer interfaces of food systems are scarcely controllable. This often leads to an indefinite contribution on the network properties. Developing hybrid artificial systems by using inert particles with a well-defined coating represents a new approach in food science. Coating with functionalized silanes enables the imitation of naturally occurring chemical groups. A novel experimental approach involving nano- and macroscopic analytical techniques (X-ray photoelectron spectroscopy and contact angle) sheds light on the nature and the strength of the adsorption. Depending on the presented surface functionality, strong specific to weak unspecific adsorptions arise, e.g. amino-functionalized surfaces show strong interaction with protein, while almost no interaction was observed with an aliphatic surface. Based on these different particle adhesivenesses, the monitoring of network formation discloses a significant impact of particle surface functionality on network development of food matrixes. An increasing network development time (3.2–6.0 min, gluten protein-based) in combination with a decreasing network strength (874-464 mNm gluten protein-based) correlates with an increasing adhesiveness of particles. Thus, using functionalized particles clearly demonstrates the importance of particle surface functionality on network properties in food systems. Graphical abstract: Image 1